Soil carbon and nitrogen pools under perennial forage - Widiastuti, Dwi P., author; Davis, Jessica G., advisor; Mikha, Maysoon M., committee member; Qian, Yaling, committee member (Colorado State University. Libraries, 2010)
To view the abstract, please see the full text of the document.
Keywords: Soil biochemistry; Soils -- Carbon content; Soils -- Nitrogen content; Carbon cycle (Biogeochemistry)